Sema3A inactivates the ERK/JNK signalling pathways to alleviate inflammation and oxidative stress in lipopolysaccharide-stimulated rat endothelial cells and lung tissues. (31st December 2023) - Qiu, Qianwen; Yu, Xiufeng; Chen, Qingli; He, Xuwei
Abstract: Semaphorin 3A (Sema3A) is a secretory member of the semaphorin family of immune response regulators. This research focuses on its effects on inflammation and oxidative stress in acute respiratory distress syndrome (ARDS). By analysing the GEO dataset GSE57011, we obtained Sema3A as the most downregulated gene in ARDS samples. Lipopolysaccharide (LPS) was used to stimulate rat pulmonary microvascular endothelial cells (PMVECs) and rats to induce ARDS-like symptoms in vitro and in vivo, respectively. LPS induced severe damage in rat lung tissues, in which reduced immunohistochemical staining of Sema3A was detected. Sema3A overexpression reduced apoptosis and angiogenesis of LPS-induced PMVECs and alleviated lung injury and pulmonary edoema of rats. Moreover, ELISA results showed that Sema3A overexpression downregulated the levels of inflammatory cytokines and oxidative stress markers both in PMVECs and the rat lung. Activation of ERK/JNK signalling aggravated LPS-induced damage on PMVECs; however, the aggravation was partly blocked by Sema3A, which suppressed phosphorylation of ERK/JNK. Overall, this study demonstrates that Sema3A inactivates the ERK/JNK signalling to ameliorate inflammation and oxidative stress in LPS-induced ARDS models. Sema3A might therefore represent a candidate option for ARDS treatment.